Next-Generation Sequencing of CYP2C19 in Stent Thrombosis: Implications for Clopidogrel Pharmacogenomics - Morales-Rosado, Joel A.; Goel, Kashish; Zhang, Lingxin; Åkerblom, Axel; Baheti, Saurabh; Black, John L.; Eriksson, Niclas; Wallentin, Lars; James, Stefan; Storey, Robert F.; Goodman, Shaun G.; Jenkins, Gregory D.; et al. (Cardiovascular drugs and therapy, 2021)
Purpose Describe CYP2C19 sequencing results in the largest series of clopidogrel-treated cases with stent thrombosis (ST), the closest clinical phenotype to clopidogrel resistance. Evaluate the impact of CYP2C19 genetic variation detected by next-generation sequencing (NGS) with comprehensive annotation and functional studies. Methods Seventy ST cases on clopidogrel identified from the PLATO trial ( n = 58) and Mayo Clinic biorepository ( n = 12) were matched 1:1 with controls for age, race, sex, diabetes mellitus, presentation, and stent type. NGS was performed to cover the entire CYP2C19 gene. Assessment of exonic variants involved measuring in vitro protein expression levels. Intronic variants were evaluated for potential splicing motif variations. Results Poor metabolizers ( n = 4) and rare CYP2C19*8 , CYP2C19*15 , and CYP2C19*11 alleles were identified only in ST cases. CYP2C19*17 heterozygote carriers were observed more frequently in cases ( n = 29) than controls ( n = 18). Functional studies of CYP2C19 exonic variants ( n = 11) revealed 3 cases and only 1 control carrying a deleterious variant as determined by in vitro protein expression studies. Greater intronic variation unique to ST cases ( n = 169) compared with controls ( n = 84) was observed with predictions revealing 13 allele candidates that may lead to a potential disruption of splicing and a loss-of-function effect of CYP2C19 in ST cases. Conclusion NGS detected CYP2C19 poor metabolizers and paradoxically greater number of so-called rapid metabolizers in ST cases. Rare deleterious exonic variation occurs in 4%, and potentially disruptive intronic alleles occur in 16% of ST cases. Additional studies are required to evaluate the role of these variants in platelet aggregation and clopidogrel metabolism.